2019
DOI: 10.18502/jad.v12i4.356
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Features and Seroprevalence of Borrelia burgdorferi in Erzincan, Turkey

Abstract: Background: We aimed to determine the geographical features and seroprevalence of Borrelia burgdorferi in Erzincan, Turkey, which has a high tick population due to its geographical position and climatic conditions. Methods: From January to December 2014, 368 people living in Erzincan, northeastern Turkey were enrolled. B. burgdorferi IgG antibodies were investigated in the collected serum samples using the ELISA method in 2015. Positive and borderline results were confirmed using the Western Blot (WB) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A representative sample of healthy blood donors from the Tyrol region of Austria reported a seropositivity range of 1.5%–7.2% from samples confirmed by line blot ( 17 ). A regional study in Turkey among healthy volunteers revealed seropositivity of 4.1% by single-tier testing with ELISA and 2.2% confirmed by WB ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…A representative sample of healthy blood donors from the Tyrol region of Austria reported a seropositivity range of 1.5%–7.2% from samples confirmed by line blot ( 17 ). A regional study in Turkey among healthy volunteers revealed seropositivity of 4.1% by single-tier testing with ELISA and 2.2% confirmed by WB ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen articles reported seroprevalence of LB in four countries in Southern Europe (Güneş et al 2005 , Tomao et al 2005 , Krstić and Stajković 2007 , Bozkurt et al 2008 , Kaya et al 2008 , Uyanık et al 2009 , Di Renzi et al 2010 , Oteiza-Olaso et al 2011 , Aslan Başbulut et al 2012 , Jovanovic et al 2015 , Parlak et al 2015 , Bucak et al 2016 , Gazi et al 2016 , Cora et al 2017 , Akar et al 2019 , Cikman et al 2019 , Lledo et al 2019 , Barreiro-Hurle et al 2020 ). All studies reported subnational rather than country-wide estimates ( Table 3 ); 15 reported seroprevalence in groups at high risk of tick exposure based on occupation or residential area, and 11 reported on populations at low risk.…”
Section: Resultsmentioning
confidence: 99%
“…The weighted mean seroprevalence of LB in Southern Europe among studies that used (standard) two-tier testing strategies in general populations (Tomao et al 2005 , Kaya et al 2008 , Di Renzi et al 2010 , Aslan Başbulut et al 2012 , Jovanovic et al 2015 , Parlak et al 2015 , Bucak et al 2016 , Cora et al 2017 , Akar et al 2019 , Cikman et al 2019 , Barreiro-Hurle et al 2020 ) was 3.9% ( Table 7 ). The standard IgM and IgG weighted mean seroprevalence was 5.7% in high-risk groups versus 3.9% in low-risk groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation